Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

If (1/6) – x = 1/6, then x = . If (1/6) – x = 1/6, then x = .

 If (1/6) – x = 1/6, then x =                                   .
 If (1/6) – x = 1/6, then x =                                   .

Grade:12

1 Answers

Anand Kumar Pandey
askIITians Faculty 5608 Points
4 months ago
Dear Student

Consider the given equation, (1/6)–x = 1/6
Transpose–x to RHS then it becomes x and 1/6 to LHS then it becomes–1/6
x = 1/6–1/6
x= 0
Then, the value of x = 0

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free

10th iCAT Scholarship Test Registration Form